Meningkatkan Kemampuan Membaca Permulaan melalui Metode SAS di MIS Hidayatul Mubtadiin - A’yuni, Nurrotul; Hikmah, Nurul; S, Nur Santi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ early reading skills through the implementation of the Structural Analytical Synthetic (SAS) method at MIS Hidayatul Mubtadiin. The SAS method was chosen because it focuses on recognizing whole words before analyzing them into smaller parts, making it easier for students to understand word structures and enhance their reading skills. This research employed a classroom action research (CAR) method with two cycles, involving planning, implementation, observation, and reflection stages. The study subjects were first-grade students who struggled with early reading skills. Data were collected through observations, interviews, reading tests, and questionnaires, then analyzed descriptively using both qualitative and quantitative approaches. The findings indicate that the SAS method significantly improved students’ early reading skills. In the first cycle, students showed progress in recognizing and pronouncing simple words, although challenges remained in pronunciation and word comprehension. In the second cycle, a more significant improvement was observed, as students were able to read simple sentences more fluently and understand the reading content. The questionnaire results revealed that students felt more confident and motivated in learning to read using the SAS method compared to conventional methods. However, challenges such as varying levels of student comprehension and time constraints in lessons were also identified. Therefore, more diverse teaching strategies and better time allocation are needed to optimize the effectiveness of the SAS method in enhancing students’ early reading skills.